Studies on Fern of Lesser Sunda Islands I: Checklist of the Genus Adiantum (Pteridaceae) - Lestari, Wenni Setyo; Adjie, Bayu (Jurnal Biodjati, 2020)
Adiantum or maidenhair fern is one of the largest genera in Pteridaceae. We survey their species diversity in Lesser Sunda Islands, Indonesia through the living collection and herbarium examination. SeventeenÂ species of AdiantumÂ wereÂ recorded. including fiveÂ species thatÂ considered as introduced and naturalizedÂ species. One species that grows naturally, Adiantum silvaticum,Â were previously known as endemic to Australia.Â However,Â this study revealedÂ theÂ new distribution of this species on Sumba and Flores.